Teleneurology by internet and telephone a study of medical self-help - Larner, A. J. (Springer, 2011)
Medical information is now widely available on the Internet and through telephone helplines such as NHS Direct and the focus on patient self care is likely to increase. Clinicians in all specialties will often encounter patients who have made self-directed searches for medical information prior to the clinical encounter. Teleneurology by Internet and Telephone is a study of patient information-seeking behaviour in neurology patients prior to referral from primary to secondary care. The book analyses frequency of Internet access and use, and of telephone helpline awareness and use. It also explores use of these modalities over time, use according to patient gender and age and by gender and age over time.  Teleneurology by Internet and Telephone is an accessible overview of the utility of these modalities of health information provision and will be of interest not only to neurologists and clinicians in other specialities but also to public health researchers, sociologists and political scientists with an interest in questions of health care provision.